The Determinants Factor on Repurchase Intentions: A Study from Developing Economies - Siti Ummi Arfah Nasution; Siti Wardah Praditina Nasution (International Journal of Management Science and Application, 2023)
Changes in consumer lifestyles must be a particular concern in identifying aspects of marketing in finding new target markets as one of the trends that have become the favourite of society in developing economies, i.e., shopping trends. This study focuses more on examining the effect of visual merchandising, store atmosphere, and impulse buying as a determinant and implication towards the consumer's repurchase intentions. The research uses causal-comparative type, which involves the consumer with 100 respondents from March until July 2020. The analysis method uses structural equation modelling with the confirmatory factor analysis technique. The results show that determining factor on Repurchase Intentions is empirical evidence that visual merchandising directly affects impulse buying and re-purchasing. On the other hand, store atmosphere fails to predict impulse buying and re-purchasing. Impulse buying directly impacts the repurchase intentions. Impulse buying is also a determining factor as a mediator between Visual Merchandising and Repurchase Intentions as an indirect, although Store Atmosphere is non-significant as a determining factor. The impulsive buying factor can be used as an alternative strategy to boost sales in the short term from the repurchase results.